Acute phase of depression treatment - current research and its perspectives on Jessenius Faculty of Medicine - Oppa M.; Kulhan T.; Nosáľová G.; Ondrejka I. (Sciendo, 2016)
In the previous research at Jessenius Faculty of Medicine in Martin has been studied depression and its treatment from the aspects of the quality of life and functioning of the patients, as well as comparing the efficacy and safety of venlafaxine versus venlafaxine and olanzapine treatment. Last years have been studied the parameters of the autonomic nervous system in the context of depression. Our new work will build on these findings, during the exploration of efficacy and safety of a novel antidepressant vortioxetine in monotherapy and in combination with olanzapine. Since combination of vortixetine and olanzapine is not yet understood, it is unknown whether the effect of the treatment of depressive symptoms and associated problems will be stronger and faster compared to vortioxetine monotherapy.